2022
DOI: 10.1021/acscatal.2c02258
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility Regulation of Loops Surrounding the Tunnel Entrance in Cytochrome P450 Enhanced Substrate Access Substantially

Abstract: In recent years, the engineering of flexible loops to improve enzyme properties has gained attention in biocatalysis. Herein, we report a loop engineering strategy to improve the stability of the substrate access tunnels, which reveals the molecular mechanism between loops and tunnels. Based on the dynamic tunnel analysis of CYP116B3, five positions (A86, T91, M108, A109, T111) in loops B-B′ and B′-C potentially affecting tunnel frequent occurrence were selected and subjected to simultaneous saturation mutagen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 49 publications
1
40
0
Order By: Relevance
“…Therefore, we reasoned that the peroxygenase activity of P450s could be improved by engineering some of the water tunnels on the basis of the reported tunnel engineering strategy to ensure suitable inflow pathways for water-soluble H 2 O 2 (Figure ). In this study, we have designed and broadened the water tunnels of P450s to facilitate the H 2 O 2 flow to the active site. These modifications significantly increase the peroxygenase activity of three P450 enzymes, including NADH-dependent CYP199A4 and CYP153A M.aq , as well as DFSM-facilitated P450BM3 peroxygenase.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we reasoned that the peroxygenase activity of P450s could be improved by engineering some of the water tunnels on the basis of the reported tunnel engineering strategy to ensure suitable inflow pathways for water-soluble H 2 O 2 (Figure ). In this study, we have designed and broadened the water tunnels of P450s to facilitate the H 2 O 2 flow to the active site. These modifications significantly increase the peroxygenase activity of three P450 enzymes, including NADH-dependent CYP199A4 and CYP153A M.aq , as well as DFSM-facilitated P450BM3 peroxygenase.…”
Section: Introductionmentioning
confidence: 99%
“…Tunnel analyses including throughput, tunnel curvature, length, and substrate were introduced to explore the improved catalytic efficiency. 47 The geometric properties of the tunnel were prominently analyzed to reveal the ligand transport process. The results showed that the average curvature of PaAmi M1…”
Section: Static and Dynamic Tunnel Analysis Of Paami M1 And Its Tripl...mentioning
confidence: 99%
“…Similarly, highly flexible loops surrounding the tunnel entrance of a cytochrome P450 were engineered to enhance its substrate access. The best variant obtained reduced the flexibility of two critical loops, responsible for improving the stability of the substrate access tunnel, and showed 134-fold improvement in the catalytic activity ( Li Z. et al, 2022 ). A loop engineering strategy was also applied to improve the activity and selectivity of a cumene dioxygenase from Pseudomonas fluorescens IP01.…”
Section: Rational Design Strategy Based On Dynamics Modificationmentioning
confidence: 99%